EFFECT OF LUMINOUS SPECTRUM AND BAP ON PLB INDUCTION FROM CALLI OF Cattleya nobilior Rchb.f. (ORCHIDACEAE) - Ramos, J. C. M.; Goelzer, A.; Damiani, C. R. (Revista Brasileira de Engenharia de Biossistemas, 2020)
This study was developed with the objective of evaluating the effect of 6-benzylaminopurine - BAP (0; 0.5 and 1.0 mg L-1) and light spectra (white, red and blue), in the induction of structures similar to the protocorms ("protocorm like bodies - PLBs") from calli obtained from leaf explants. The experimental design used was completely randomized and the treatments were arranged in a 3x3 factorial scheme (three concentrations of BAP and three light spectra), with four replicates (flask) containing five explants each. At 60 days of cultivation, the number and length of protocorms, number of leaves per protocorm, total fresh weight, percentage of oxidized explants and color of explants were evaluated, with the latter being assigned the following values: 1 - white / yellowish, 2 - light green and 3 - dark green. From the results obtained it was possible to conclude that the calli cultivation of Cattleya nobilior in MS medium supplemented with 1.0 mg L-1 of BAP and under a red light spectrum promotes an increase in fresh mass and decreases the oxidation of protocorms, while, the culture in medium containing 0.5 mg L-1 of BAP and under white light spectrum promotes a slight increase in the length of the protocorms. However, for the number of protocorms, number of leaves per protocorm and color of the protocorms, the treatments carried out did not promote significant changes on these variables.